SUSTAINABLE GROWTH IN PRIVATE ISLAMIC SCHOOLS IN SOUTHWESTERN NEGERIA: LEADERSHIP, FUNDING, AND ETHICAL INNOVATION: Pertumbuhan Berkelanjutan pada Sekolah Islam Swasta di Nigeria Barat Daya: Kepemimpinan, Pendanaan, dan Inovasi Etis - Uthman Okanlawon Sidiq (Tunas Harapan Ummat Foundation, 2026)
The persistent crisis of out-of-school children in Nigeria, a nation of over 200 million, stems largely from a shortage of public educational infrastructure, leaving the responsibility for academic oversight shared among federal, state, and local governments, as well as private entities, NGOs, and religious organizations. This qualitative study examines the plight of private Islamic schools in Southwestern Nigeria, particularly in Lagos, which face significant barriers to growth, including the proliferation of low-cost competitors, chronic underfunding, infrastructure deficits, and socio-cultural hurdles such as family interference and parental non-cooperation. Nigeria is a multi-ethnic nation organized into six geopolitical zones, with the Northeast and Northwest being predominantly Muslim, while the North-central maintains a more balanced 60/40 Christian-to-Muslim ratio. This paper focuses on the Southwest, a zone where Muslims comprise approximately 45% of the population alongside Christian and African Traditionalist communities. Drawing on primary data from Focus Group Discussions held with the Association of Model Islamic Schools in Lagos, November 2025, as well as stakeholder observations from teachers and government officials, the research argues that long-term sustainability is contingent upon a triad of sagacious leadership, consistent funding, and ethical innovation. Ultimately, the paper provides a roadmap for Muslim proprietors that emphasizes substantial reinvestment, the maintenance of rigorous standards devoid of sectarian bias, and improved staff welfare, while advocating for modernized growth strategies such as digital transformation, robust alumni networking, Public-Private Partnerships (PPP), and the pursuit of ethical funding through collaboration with Islamic financial institutions and government subventions.